An investigation of information communication and dissemination needs. Case of Gautrain Operations. - Rakabe, Manyedi; Musakwa, Walter; Gumbo, Trynos (My University, 2017)
Public transport plays an important part in the way people move around their communities. Information dissemination concerns the process of conveying information through intelligent transport systems from transport operators to commuters. Correct and timely dissemination is essential to maximize operational efficiency and reduce the effects of disruptions. Public transport operators often concentrate on the technical aspect of services while commuter needs are neglected. The Gauteng province has been making efforts in the pursuit to improve mobility; a case in point is the Gautrain. The Gautrain is the first mass rapid rail transit system in South Africa and the first in Africa. Although much effort has been made there has not been much effort in understanding the information dissemination needs of commuters. The study aimed to identify information communication and dissemination (ICD) strategies of the Gautrain and evaluate the effectiveness of those strategies. It then described the impact of information dissemination needs also analysing the level of smartness in those aspects. Questionnaires and key informative interviews were conducted in order to obtain the user's perspectives and understand their information needs. The results reveal the various dissemination tools used by the Gautrain Management Agency: Gautrain App, Social Media and Interactive Public Information Displays among others are utilised as tools to communicate with the commuters. Indicators were selected in order to measure the level of smartness on the Gautrain ICD strategies, which indicated that Gautrain was partly smart. The research highlighted how ICD strategies can enhance the overall improvement in public transport and influence user satisfaction. Lastly, the study also highlights some challenges public transport agencies face in providing adequate information to commuters such as policy disputes and demand.
Keywords: Öffentlicher Verkehr; Eisenbahn; Bahnstrecke; Pendlerverkehr; Fahrgast; Information; Kommunikationstechnologie; Informationstechnologie